Gender Differences in the Effects of Acute Stress on Spatial Ability. - Gabriel, Kara; Hong, Stephen; Chandra, Marvin; Lonborg, Susan; Barkley, Cynthia (Sex Roles, 2011)
lthough reports that men and women differ in spatial ability are common, recent research examining stress effects on spatial navigation have not included analyses of gender differences. The current study investigated cue perception and mental rotation after an acute cold-water hand immersion stress in 156 undergraduates from the western United States. Gender differences were observed in spatial performance and spatial anxiety. Discriminant analysis revealed that distal gradient cue identification and mental rotation reaction times as well as spatial anxiety differed among men and women exposed to the acute stress and their warm-water hand immersion controls. These results indicate that stress differentially alters spatial performance in men and women, and underscores the importance of assessing gender differences when examining spatial ability.